Historical biogeography of the genus Cyriocosmus (Araneae: Theraphosidae) in the Neotropics According to an Event-Based Method and Spatial Analysis of Vicariance - Ferretti, Nelson Edgardo (2012)
The distributional history of the South American endemic genus Cyriocosmus (Araneae, Theraphosidae) was reconstructed, and a spatial analysis of vicariance was conducted. Results obtained with the software RASP (Reconstruct Ancestral State in Phylogenies), suggest that Cyriocosmus originated within an area currently represented by the biogeographical subregions of the Amazonian and Paramo Punan. We found 3 vicariant nodes: the 1st into the Amazonian-Caribbean, the 2nd into the Caribbean, and the 3rd into the Amazonian-Parana, Amazonian-Chacoan, and Amazonian-Parana and Chacoan. Using the Vicariance Inference Program we found that 1 vicariant node different from that obtained with RASP, and the hypothetical barriers for the clade were represented by the Voronoi lines in South America. In order to interpret biogeographical events that affected the genus Cyriocosmus, these results are contrasted with major geological events that occurred in South America, and also with previous biogeographical hypotheses.